Raster grids of geometric capacity for peat accumulation in northwest and southern Borneo - Alexander R Cobb; Fangyi Tan; Naomi Heng Hwee Heng (PANGAEA, 2020)
This dataset contains raster grids in GeoTIFF format describing the constraints on accumulation of tropical peat imposed by drainage network geometry in regions of northwest and southern Borneo. Each raster in the dataset gives the geometric capacity for peat accumulation (non-dimensional equilibrium peat thickness) in a parcel of land, calculated using the method described in the paper. The parcels are grouped into five areas, referred to by the names Badas, Baram, Belait, EMRP and Sebangau. Rasters have arbitrary numeric labels (001.tif, 002.tif, ...) in all areas except the Badas area, where descriptive names are used for the parcels before (badas) and after (badas_west and badas_east) subdivision by a canal. The map projection and resolution are included in each raster via standard GeoTIFF metadata; the projections used were EPSG:5247 for the Badas, Baram, and Belait areas and EPSG:32749 for the EMRP and Sebangau areas.